Constrictive pericarditis heart failure in a patient with atrial fibrillation: A diagnostic challenge - Rebeca Muñoz‐Rodríguez; Aída T. Igareta‐Herraiz; María Manuela Izquierdo‐Gómez; Belén Marí‐López; María Amelia Duque‐González; Flor Baeza‐Garzón; Antonio Barragán‐Acea; Julio Miranda‐Bacallado; Francisco Bosa‐Ojeda; Juan Lacalzada‐Almeida (Clinical Case Reports, 2023)
Abstract Constrictive pericarditis is an infrequent cause of heart failure. Diagnosis is challenging and requires a high level of suspicion. Subtle echocardiographic findings, as the pericardial bounce, could be the clue to diagnosis.